PENGETAHUAN REMAJA TENTANG PUSAT INFORMASI KONSELING REMAJA (PIK-R) DI SMKS IP YAKIN JAKARTA TAHUN 2023 - Nurlindawati; Kustia Anggereni; Djimmy Heru Purnomo Babo; Tri Yunita; Jingga Ayu Maharani (PAKDEMAS : Jurnal Pengabdian Kepada Masyarakat, 2023)
This article is the result of Community Service (PKM) activities at IP Yakin Jakarta Vocational School. The team focused on PKM activities for students at the SMKS level. Methods developed in a group with the same position among members, especially based on age, status or class. The aim of PKM is to increase understanding regarding PIK-R, the impact of early marriage in adolescence on reproductive health, free sex behaviour that can cause sexually transmitted diseases including HIV/AIDS in adolescents and to know the legal basis for the PIK-R program as contained in the regulation of the head BKKBN and DKI Jakarta Governor Regulation. This PKM activity is in the form of providing health education about PIK-R, HIV/AIDS AND the legal basis of PIK-R. Evaluation of PKM activities using pre-test and post-test questionnaires. The results of this PKM are in the form of increasing knowledge, attitudes, and life skills in early marriage, preventing free sex behaviour that can transmit HIV/AIDS to adolescents and being able to demonstrate the legal basis related to PIK-R.